2019
DOI: 10.1002/jbio.201960065
|View full text |Cite
|
Sign up to set email alerts
|

Induction and measurement of the early stage of a host‐parasite interaction using a combined optical trapping and Raman microspectroscopy system

Abstract: Understanding and quantifying the temporal acquisition of host cell molecules by intracellular pathogens is fundamentally important in biology. In this study, a recently developed holographic optical trapping (HOT)-based Raman microspectroscopy (RMS) instrument is applied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…They successfully demonstrated that OT-RS is capable of monitoring the chemical reaction of single particles [39]. Very recently, Sinjab et al applied OT Raman micro-spectroscopy to detect and monitor the molecular trafficking of a specific molecular species in the single cell [40]. This study demonstrated that OT-RS could be an effective method of detecting and monitoring biological processes.…”
Section: Introductionmentioning
confidence: 87%
“…They successfully demonstrated that OT-RS is capable of monitoring the chemical reaction of single particles [39]. Very recently, Sinjab et al applied OT Raman micro-spectroscopy to detect and monitor the molecular trafficking of a specific molecular species in the single cell [40]. This study demonstrated that OT-RS could be an effective method of detecting and monitoring biological processes.…”
Section: Introductionmentioning
confidence: 87%
“…Another promising direction for label-free single-cell analysis is via measuring the inherent optical properties of cells. This has been shown in recent work such as the single-cell identification of parasites through their Raman spectra [125], the quantification of single-cell viral infection titer through Laser Force Cytology [126], and single bacteria detection via refractive index measurements [127]. Lastly, the mechanical and size properties of cells have also been exploited for identifying infected single cells.…”
Section: Label-free Analysismentioning
confidence: 98%
“…76 More broadly in biology, it is fundamentally crucial to understand the temporal interactions of host and pathogens, where Raman spectroscopy can be employed to monitor the molecular trafficking at the single cell level in real-time. 142,143 Examples include tracking temporal changes in tissue composition upon bacterial infection, determining the outcome of infections. 144 Spatial Tissue Profiling.…”
Section: Single-cell Identification Using Sers and Ml: Bacterial Iden...mentioning
confidence: 99%
“…Supervised classification analysis revealed variations in lipid, nucleic acid, and collagen content resulting from each therapy, consistent with their distinct mechanisms of action . More broadly in biology, it is fundamentally crucial to understand the temporal interactions of host and pathogens, where Raman spectroscopy can be employed to monitor the molecular trafficking at the single cell level in real-time. , Examples include tracking temporal changes in tissue composition upon bacterial infection, determining the outcome of infections …”
Section: Single-cell Identification Using Sers and Ml: Bacterial Iden...mentioning
confidence: 99%